Problems faced by Powerloom owners with respect to Somanurcluster, Coimbatore District, Tamil Nadu State - Nateson , C. (Gyan Management Journal, 2011)
This research aims to uncover the problem faced by the power loom owners in the somanur cluster, Coimbatore district, Tamil Nadu state. The data were collected from 483 Employers in and around Somanur cluster ( own producers & contract producers). The result of the personal survey conducted among the producer shows that employee and power shortage were the key factors affecting adversely the working of power loom sector and where as raw materials have limited influence on slowing down of this sector.